Places of quiet beauty : parks, preserves, and environmentalism - Conard, Rebecca (Iowa City : University of Iowa Press, 1997)
Resource protection and public recreation policies have always been subject to the shifting winds of management philosophy governing both national and state parks. Somewhere in the balance, however, parks and preserves have endured as unique places of mind as well as matter. Places of Quiet Beauty allows us to see parks and preserves, forests and wildlife refuges & mdash;all those special places that the term & ldquo;park & rdquo; conjures up & mdash;as measures of our own commitment to caring for the environment. In this broad-ranging book, historian Rebecca Conard examines the complexity of.
Foreword / Wayne Franklin -- Prologue -- Conservation Parks -- Pammel's Way -- Reshaping Park and Conservation Goals in the 1920s -- Toward a Resource Agency: The Twenty-five-Year Conservation Plan -- Seeking Balance -- The Center Does Not Hold -- The Lightning Rod Decades -- Epilogue -- Appendix: State Lands in Parks and Preserves, 1918-1996.
Includes bibliographical references (pages 355-368) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Nature conservation -- Iowa -- History; Parks -- Iowa -- History; Natural areas -- Iowa -- History; Environmentalism -- Iowa -- History; Nature -- Conservation -- Iowa -- Histoire; Réserves naturelles -- Iowa -- Histoire; Environnementalisme -- Iowa -- Histoire; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; SCIENCE -- Environmental Science; Environmentalism; Natural areas; Nature conservation; Parks; Iowa; Earth & Environmental Sciences; Ecology; parken; parks; tuinen; gardens; architectuur; architecture; Public Green and Parks; Openbare parken en groenvoorzieningen; History